The cost channel reconsidered: a comment using an identification-robust approach - Gabriel, V. J.; Martins, L. F. (Journal of Money, Credit and Banking, 2010)
We reexamine the empirical relevance of the cost channel of monetary policy (e.g., Ravenna and Walsh 2006), employing recently developed moment-conditions inference methods, including identification-robust procedures. Using U.S. data, our results suggest that the cost channel effect is poorly identified and we are thus unable to corroborate the previous results in the literature.